Using EMR to improve compliance with clinical practice guidelines for management of stable COPD. Issue 11 (November 2015) - Terasaki, Jordan; Singh, Gurinder; Zhang, Wei; Wagner, Penny; Sharma, Gulshan
Abstract: Background: Clinical practice guidelines are underutilized in the outpatient management of chronic obstructive pulmonary disease (COPD). We hypothesize that a structured approach using the electronic medical record (EMR) will improve compliance with clinical practice guidelines for the evaluation and management of patients with stable COPD. Methods: Clinical records were evaluated in a pre- and post-intervention analysis of patients with COPD seen in our pulmonary clinics at a single tertiary care academic setting. Patient charts were retrospectively screened for the diagnosis of COPD and individually assessed for a diagnosis of COPD by spirometry. We then developed and implemented a COPD Flowsheet based on clinical practice guidelines into each outpatient clinic encounter for COPD with repeat chart review of clinic patients. Improvement in the pre- to post-intervention quality metrics were compared using t-test and Chi squared as indicated. A p-value of <0.05 was considered significant. Results: A total of 200 patients were screened in the pre-intervention period and 347 in the post-intervention period. Of these, 144 (72%) and 267 (77%) met criteria for COPD based on FEV1 /FVC < 0.70, respectively. There was a significant increase in the use of severity assessment by BODE index (13.2% vs 32.2%, p-value < 0.001), inhaler technique teaching (35.4% vs 65.2%, p-value < 0.001), osteoporosis screening (20.8% vs 44.9%, p-value < 0.001) and influenza vaccination (74.3% vs 83.5%, p-value = 0.03) in post intervention period. Conclusions: Implementation of a standardized COPD Flowsheet developed from clinical practice guidelines improves advanced assessment of patients with COPD and other quality of care measures. Highlights: A structured approach was used through the EMR to implement a COPD Flowsheet. Clinical records of COPD patients were evaluated for quality measures. Standardized COPD Flowsheet improves advanced assessment of patients with COPD.